Retinal nerve fibre layer thinning is associated with worse visual outcome after optic neuritis in children with a relapsing demyelinating syndrome. (11th April 2018) - Eyre, Michael; Hameed, Aasim; Wright, Sukhvir; Brownlee, Wallace; Ciccarelli, Olga; Bowman, Richard; Lim, Ming; Wassmer, Evangeline; Thompson, Dorothy; Hemingway, Cheryl; Hacohen, Yael
Abstract : Aim: Optic neuritis may be monophasic or occur as part of a relapsing demyelinating syndrome (RDS), such as multiple sclerosis, aquaporin‐4 antibody (AQP4‐Ab) neuromyelitis optical spectrum disorder (NMOSD), or myelin oligodendrocyte glycoprotein antibody (MOG‐Ab)‐associated disease. The aims of this study were to test whether clinical, electrophysiological, and microstructural parameters differ in multiple‐sclerosis‐associated optic neuritis (MS‐ON) and antibody‐associated optic neuritis (Ab‐ON); to identify the clinical and paraclinical characteristics of children suffering worse long‐term visual outcome of RDS‐optic neuritis; and to explore the relationship between RNFL thickness and clinical parameters in RDS‐optic neuritis. Method: Forty‐two children with optic neuritis were retrospectively studied: 22 with multiple sclerosis (MS‐ON) and 20 with antibody‐associated demyelination (Ab‐ON: MOG‐Ab=16 and AQP4‐Ab=4). Clinical and paraclinical features were analysed. Results: Complete recovery of visual acuity was reported in 25 out of 42 children; eight out of 38 (21%) suffered moderate or severe visual impairment (logarithm of the minimum angle of resolution [logMAR]>0.5) in their worse eye, including four out of 38 who were blind (logMAR>1.3) in their worse eye (two with multiple sclerosis, two with AQP4‐Ab NMOSD). None of the children with MOG‐Ab were blind. Recurrence of optic neuritis was more common in the Ab‐ON group than the MS‐ON group (15 out of 20 vs seven out of 22, p =0.007). Retinal nerve fibre layer (RNFL) thickness at baseline inversely correlated with visual acuity at final follow‐up ( r =−0.41, p =0.008). There was no significant relationship between the number of episodes of optic neuritis and mean RNFL ( r =−0.08, p =0.628), nor any significant relationship between the number of episodes of optic neuritis and visual impairment ( r =0.03, p =0.794). Interpretation: In children with RDS, long‐term visual impairment inversely correlated with RNFL thickness, but not with the number of relapses of optic neuritis. Optical coherence tomography may have a role in assessing children with optic neuritis to monitor disease activity and inform treatment decisions. What this paper adds: Long‐term visual impairment is reported in 40% of children with a relapsing demyelinating syndrome following optic neuritis. Relapse of optic neuritis, occurring more frequently in the non‐multiple‐sclerosis group. Retinal nerve fibre layer thinning is associated with worse visual outcome. Optical coherence tomography can be used alongside clinical parameters as an objective measure of neuroretinal loss. What this paper adds: Long‐term visual impairment is reported in 40% of children with a relapsing demyelinating syndrome following optic neuritis. Relapse of optic neuritis, occurring more frequently in the non‐multiple‐sclerosis group. Retinal nerve fibre layer thinning is associated with worse visual outcome. Optical coherence tomography can be used alongside clinical parameters as an objective measure of neuroretinal loss. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations. This article is commented on by Pang on pages1195–1196 of this issue. Video Podcast:https://www.youtube.com/watch?v=cCmx9bUw8CU&t=4s